2020
DOI: 10.1016/j.nimb.2020.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of the Two-Temperature Model for Molecular Dynamics simulations of collisions cascades in Si and Ge

Abstract: The sensitivity of collision cascades simulations to the Two-Temperature Model main parameters is investigated by performing an extensive statistical study both in Si and Ge materials. The purpose is to identify the parameters of the Two-Temperature Model whose impact is the most significant on the cascades properties and to discuss the physical role of each parameter. We demonstrate that the electronic stopping power and electron phonon coupling have a drastic impact both in Si and Ge but that these two param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…A value of twice the cohesive energy is often taken to define v 0 [9,40], although there is no strong physical basis for this choice. Linear stopping manifests from velocities, where atom motion is uncorrelated with that of host atoms, up to the electronic Fermi velocity v F [32].…”
Section: Two-temperature Mds (2t-md)mentioning
confidence: 99%
See 1 more Smart Citation
“…A value of twice the cohesive energy is often taken to define v 0 [9,40], although there is no strong physical basis for this choice. Linear stopping manifests from velocities, where atom motion is uncorrelated with that of host atoms, up to the electronic Fermi velocity v F [32].…”
Section: Two-temperature Mds (2t-md)mentioning
confidence: 99%
“…The parameters (C e , G ep , and κ) depend on the electronic temperature, atomic temperature, structure, and density. Nonetheless, the role of electronic temperature on C e and G ep is predominant for cascade simulations [38,40]. Equation ( 3) is solved discretely, with sources and diffusion occurring in and between cells (or voxels) which are commensurate with corresponding cells in the atomic system.…”
Section: Two-temperature Mds (2t-md)mentioning
confidence: 99%
“…First, it applies the electronic stopping such as a projectile would experience in a uniform electron gas and thus effects such as channeling are not taken into account [66]. Second, many parameters are included for which there is little experimental data, making it difficult to obtain reliable results and predictability [67].…”
Section: B Including Electronic Stopping In MDmentioning
confidence: 99%
“…To get a good statistical average, for each MD setting, 78 different cascades are run with different initial PKA directions chosen according to the procedure outlined in reference [67]. The PKA is chosen such that its initial velocity vector points as much as possible toward the center of the interior region to keep the collision damage into the box and preventing atoms from leaving the interior during the cascade.…”
Section: Collision Cascade MD Simulationsmentioning
confidence: 99%
“…Some studies have shown that the direction-dependence of the electronic stopping can influence the collision cascades [118]. Other studies have demonstrated that the formation of thermal spikes and therefore of amorphous pockets is sensitive to the electronic specific heat [199] and others that the choice of the model employed for the inclusion of the electronic effects and in particular the overestimation (or underestimation) of electron-phonon coupling can have a significant influence on the number of defects created [171].…”
Section: Improving the Model For Solar Cell Degradation Via A Multisc...mentioning
confidence: 99%